The Virasoro Algebra and Some Exceptional Lie and Finite Groups - Tuite, M.P. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We describe a number of relationships between properties of the vacuum Verma module of a Virasoro algebra and the automorphism group of certain vertex operator algebras. These groups include the Deligne exceptional series of simple Lie groups and some exceptional finite simple groups including the Monster and Baby Monster.